Risiko Koalisi Gemuk Dalam Sistem Presidensial Di Indonesia - Idul Rishan (Fakultas Hukum Universitas Islam Indonesia, 2020)
This study focuses on the risk of a fat coalition in the presidential system in Indonesia. This research aims to obtain three things. First, the reasons for the emergence of fat coalitions in the presidential system. Second, the risks that fat coalitions pose to presidential systems. Third, offer a concept to restore executive and legislative relations. The research method is a doctrinal legal research with a secondary database. The results of the study concluded: first, three things were the reasons for the formation of the fat coalition. 1) The results of amendments to the Constitution that are inconsistent with the strengthening of the presidential system. 2) Due to extreme multiparty system. 3) Due to the weak ideological basis of the party. Second, the risks posed include, among other things, compromise, unstable, and close to authoritarian temptation. Third, this study offers the purification of the presidential system through changes to the Constitution and simplification of political parties.